Preparation method of phase change thermal insulation fiber based on porous structure

By adopting a phase-change insulation and thermal insulation fiber preparation method with a porous structure in the fiber, the problems of poor functional stability and influence on the mechanical properties of the fiber in the prior art are solved, and the good mechanical properties and excellent thermal insulation properties of the fiber are achieved.

CN119507062APending Publication Date: 2025-02-25BANGTE YUNXIAN (QINGDAO) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411379055.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the prior art improves the thermal insulation performance of fibers, the functional stability is poor and has an impact on the mechanical properties of the fibers. The preparation of porous fibers depends on special spinning equipment, which limits the universality and practicality of the technology.

Method used

The preparation method of phase change insulation and thermal insulation fiber based on porous structure is adopted, and the phase change insulation fiber is prepared by the preparation of nanoporous hydroxyapatite microspheres, the adsorption of phase change materials, the modification of shell materials and the preparation of modified phase change materials, and the modified phase change materials are formed, and the phase change insulation and thermal insulation fiber is prepared by spinning technology.

Benefits of technology

It achieves good mechanical properties and excellent thermal insulation properties of fibers, and has stable functions, and is suitable for outdoor products and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069420990000111
    Figure BDA0005069420990000111
Patent Text Reader

Abstract

The invention belongs to the technical field of fibers, and particularly relates to a preparation method of a phase-change heat-preservation and heat-insulation fiber based on a porous structure, and the preparation method comprises the steps of preparation of nano-porous hydroxyapatite microspheres, preparation of a core material, preparation of a shell material, preparation of a modified phase-change material and spinning. The phase-change material is modified, the modified phase-change material has a unique shell-core structure, nano porous hydroxyapatite microspheres in the core material can adsorb the phase-change material, and dual assurance of porous structure heat preservation and phase-change active heat absorption and release is achieved; the shell material is safe and environment-friendly, and is cross-linked, polymerized, grafted and coated on the surface of the core material, so that the loss of the phase-change material adsorbed in the core material is reduced, the stability of a hole network structure of the core material is ensured, and the damage to the core material structure in the spinning process is reduced. The prepared phase-change heat-preservation and heat-insulation fiber is good in mechanical property and excellent in heat-preservation and heat-insulation performance, and can be widely applied to the fields of outdoor products and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber technology, and in particular relates to a method for preparing a phase-change thermal insulation fiber based on a porous structure. Background Art

[0002] With the upgrading of consumption and the extension of product application scenarios, consumers' requirements for fabrics are constantly increasing, and the market for functional fibers is becoming broader. In recent years, outdoor sports have gradually become a new trend, and thermal insulation fibers used in outdoor clothing, sleeping bags, etc. have also received more attention. In the existing technology, the following two methods are mainly used to improve the thermal insulation performance of fibers:

[0003] (1) Adding functional additives such as ginger extract and phase change materials before spinning can improve the warmth retention function of the fiber to a certain extent. However, the same additive has different retention rates in the spinning process of different fiber substrates, resulting in poor functional stability and affecting the performance of the fiber to a certain extent.

[0004] (2) Porous fibers are prepared through melt spinning, microfluidic spinning, electrospinning and other processes. However, the porous fiber structure prepared by this method depends largely on the special design of the spinning equipment, which limits the universality and practicality of the technology to a certain extent.

[0005] In order to adapt to and meet the needs of consumers, more and more different types of fibers are required to have the functions of warmth preservation and heat insulation. In view of this, a preparation method of phase change thermal insulation fiber based on porous structure is proposed. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a phase change thermal insulation fiber based on a porous structure, so as to achieve the invention purpose of stabilizing the thermal insulation functionality and not affecting the mechanical properties of the fiber.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing a phase-change thermal insulation fiber based on a porous structure comprises the following steps:

[0009] S1. Preparation of nanoporous hydroxyapatite microspheres

[0010] Span-80 is added to cyclohexane and stirred for 10 to 20 minutes to obtain an oil phase, and a diammonium phosphate solution with a pH adjusted is added to the oil phase and quickly stirred for 20 to 30 minutes to obtain an emulsion; the emulsion is added to a calcium nitrate tetrahydrate solution and stirred for 10 to 20 minutes, and then heated in a water bath to 38 to 45°C, reacting while stirring, and after the reaction is completed, rotary evaporation and centrifugation are performed to obtain a crude product, and the crude product is washed with cyclohexane, acetone and anhydrous ethanol in turn, and vacuum dried to obtain nanoporous hydroxyapatite microspheres.

[0011] Preferably, the volume ratio of span-80 to cyclohexane is 1:15-18.

[0012] Preferably, the pH of the diammonium phosphate solution is adjusted using a 0.6 mol / L ammonia solution.

[0013] Preferably, the concentration of the diammonium phosphate solution is 0.3-0.5 mol / L, and the pH is 10-11.

[0014] Preferably, the mass ratio of the diammonium phosphate solution to the oil phase is 1:1.7-2.1.

[0015] Preferably, the concentration of the calcium nitrate tetrahydrate solution is 0.4-0.6 mol / L, and the mass ratio of the calcium nitrate tetrahydrate solution to the emulsion is 1.8-2.2:1.

[0016] Preferably, the reaction time is 20 to 28 hours.

[0017] Preferably, the stirring rate is 400-600 r / min, and the rapid stirring rate is 1100-1300 r / min.

[0018] Preferably, the nanoporous hydroxyapatite microspheres have an average particle size of 160 to 230 nm and a porosity of 75 to 82%.

[0019] S2. Preparation of core materials

[0020] The phase change material is dissolved in chloroform, and then nanoporous hydroxyapatite microspheres are added and stirred for 20 to 30 minutes. After standing for 1 to 2 hours, the phase change material is adsorbed in the porous structure of the nanoporous hydroxyapatite microspheres, and the core material is obtained by reduced pressure evaporation, filtration and drying.

[0021] Preferably, the phase change material is one or more of stearic acid, hexadecane and octadecane.

[0022] Preferably, the volume ratio of the phase change material to chloroform is 1:7-9.

[0023] Preferably, the added amount of the nanoporous hydroxyapatite microspheres is 24-32% of the mass of the phase change material.

[0024] Preferably, the temperature of the reduced pressure evaporation is 50-60° C. and the time is 20-30 min.

[0025] Preferably, the drying temperature is 70-80° C. and the drying time is 6-8 hours.

[0026] S3. Preparation of shell materials

[0027] Add polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene and perform azeotropic distillation to remove water, then evaporate the toluene, cool to room temperature, add dichloromethane under nitrogen protection until the system is clarified, and then drop acid-binding agent triethylamine and acryloyl chloride to the system in sequence under ice bath conditions. After the dropwise addition is completed, react at room temperature for 24 to 36 hours to modify the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer with unsaturated double bonds. After the reaction is completed, pour into ether for precipitation, filter, redissolve the precipitated product in dichloromethane, and then precipitate with ether, filter, and dry to obtain the shell material.

[0028] Preferably, the volume ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene is 1:3-5; the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is purchased from Guangzhou Carbon Water Technology Co., Ltd.

[0029] Preferably, the temperature of the ice bath is 4-8°C.

[0030] Preferably, the molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, triethylamine and acryloyl chloride is 1:8-10:8-10.

[0031] Preferably, the dripping rate is 2-5 ml / min.

[0032] Preferably, the drying temperature is 60-70° C. and the drying time is 6-8 hours.

[0033] S4. Preparation of modified phase change materials

[0034] The core material and the shell material are added into distilled water and stirred, and ammonium cerium nitrate is added and ultrasonically reacted for 2 to 3 hours under nitrogen protection. After the reaction, the modified phase change material is obtained by centrifugation, filtration, water washing and drying.

[0035] Preferably, the mass ratio of the core material to the shell material is 30-40:13-17; and the amount of the ammonium cerium nitrate added is 1.6-2.4% of the shell material.

[0036] Preferably, the temperature of the ultrasonic reaction is 40-45° C., and the frequency is 120-160 kHz.

[0037] Preferably, the drying temperature is 70-80° C. and the drying time is 6-8 hours.

[0038] The core material is nanoporous hydroxyapatite microspheres adsorbed with phase change material, the surface of the nanoporous hydroxyapatite microspheres contains hydroxyl groups, the shell material is polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer modified with unsaturated double bonds, under the action of the initiator ammonium cerium nitrate, the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is free radical cross-linked and polymerized and grafted to the nanoporous hydroxyapatite microspheres, and is coated on the surface of the nanoporous hydroxyapatite microspheres to form a cross-linked network structure, thereby obtaining a modified phase change material with a core-shell structure.

[0039] S5. Spinning

[0040] The modified phase change material is added into the spinning solution or the polymer slice and mixed evenly, and the phase change thermal insulation fiber is obtained after wet spinning or melt spinning.

[0041] Preferably, the spinning solution is one of a viscose spinning solution and a polyacrylonitrile spinning solution.

[0042] Preferably, the polymer slice is one of PP slice, PET slice and PA6 slice.

[0043] Preferably, the added amount of the modified phase change material is 2-5wt% of the effective ingredients or polymer chips in the spinning solution; the effective ingredients of the viscose spinning solution refer to the methyl cellulose content in the viscose spinning solution.

[0044] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are:

[0045] 1. The phase change thermal insulation fiber prepared by the present invention has good mechanical properties and excellent thermal insulation properties, and can be widely used in outdoor products and other fields.

[0046] 2. The present invention modifies the phase change material, and the modified phase change material has a unique core-shell structure, wherein the nanoporous hydroxyapatite microspheres in the core material can adsorb the phase change material, achieving the dual guarantee of thermal insulation of the porous structure and active heat absorption and release of heat during phase change; the shell material is safe and environmentally friendly, cross-linked and polymerized and grafted onto the surface of the core material, reducing the loss of the phase change material adsorbed inside the core material, ensuring the stability of the core material pore network structure, and reducing the damage to the core material structure during the spinning process.

[0047] 3. The dispersibility and compatibility of nanoporous hydroxyapatite microspheres and phase change materials with spinning raw materials are relatively poor, while the shell material makes up for this defect, which not only avoids the influence of direct addition of core materials or phase change materials on the mechanical properties of the fiber, but also realizes the durability of the fiber's thermal insulation function. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with specific embodiments.

[0049] Example 1

[0050] S1. Preparation of nanoporous hydroxyapatite microspheres

[0051] Span-80 was added to cyclohexane and stirred for 15 minutes to obtain an oil phase. Ammonium dihydrogen phosphate solution with adjusted pH was added to the oil phase and quickly stirred for 25 minutes to obtain an emulsion. The emulsion was added to calcium nitrate tetrahydrate solution and stirred for 15 minutes, then heated to 40°C in a water bath and reacted while stirring. After the reaction was completed, a crude product was obtained by rotary evaporation and centrifugation. The crude product was washed with cyclohexane, acetone and anhydrous ethanol in turn, and vacuum dried to obtain nanoporous hydroxyapatite microspheres.

[0052] The volume ratio of span-80 to cyclohexane is 1:17.

[0053] The pH of the diammonium phosphate solution was adjusted using a 0.6 mol / L ammonia solution.

[0054] The concentration of the diammonium phosphate solution is 0.4 mol / L, and the pH is 10.5.

[0055] The mass ratio of the diammonium phosphate solution to the oil phase is 1:1.9.

[0056] The concentration of the calcium nitrate tetrahydrate solution is 0.5 mol / L, and the mass ratio of the calcium nitrate tetrahydrate solution to the emulsion is 2:1.

[0057] The reaction time is 24h.

[0058] The stirring rate is 500 r / min, and the rapid stirring rate is 1200 r / min.

[0059] The nanoporous hydroxyapatite microspheres have an average particle size of 200 nm and a porosity of 82%.

[0060] S2. Preparation of core materials

[0061] The phase change material was dissolved in chloroform, and then nanoporous hydroxyapatite microspheres were added and stirred for 25 minutes. After standing for 1.5 hours, the phase change material was adsorbed into the porous structure of the nanoporous hydroxyapatite microspheres. The core material was obtained by reduced pressure evaporation, filtration and drying.

[0062] The phase change material is stearic acid.

[0063] The volume ratio of the phase change material to chloroform is 1:8.

[0064] The added amount of the nanoporous hydroxyapatite microspheres is 28% of the mass of the phase change material.

[0065] The temperature of the reduced pressure evaporation is 55° C. and the time is 25 min.

[0066] The drying temperature is 75° C. and the drying time is 7 hours.

[0067] S3. Preparation of shell materials

[0068] Add polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene and perform azeotropic distillation to remove water, then evaporate the toluene, cool to room temperature, add dichloromethane under nitrogen protection until the system is clarified, and then drop acid-binding agent triethylamine and acryloyl chloride to the system in sequence under ice bath condition. After the dropwise addition, react at room temperature for 30 hours to modify unsaturated double bonds in the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer. After the reaction, pour into ether for precipitation, filter, redissolve the precipitated product in dichloromethane, and then precipitate with ether, filter and dry to obtain the shell material.

[0069] The volume ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene is 1:4; the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer was purchased from Guangzhou Carbon Water Technology Co., Ltd.

[0070] The temperature of the ice bath was 6°C.

[0071] The molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, triethylamine and acryloyl chloride is 1:9:9.

[0072] The dropping rate is 3 ml / min.

[0073] The drying temperature is 65° C. and the drying time is 7 hours.

[0074] S4. Preparation of modified phase change materials

[0075] The core material and the shell material were added into distilled water and stirred, and ammonium cerium nitrate was added and ultrasonically reacted for 2.5 hours under nitrogen protection. After the reaction, the modified phase change material was obtained by centrifugation, filtration, water washing and drying.

[0076] The mass ratio of the core material to the shell material is 35:14; the added amount of the ammonium cerium nitrate is 1.9% of the shell material.

[0077] The drying temperature is 75° C. and the drying time is 7 hours.

[0078] The temperature of the ultrasonic reaction was 42°C and the frequency was 140 kHz

[0079] S5. Spinning

[0080] The modified phase change material was added into the viscose spinning solution and uniformly mixed for 20 minutes, and the phase change thermal insulation fiber was obtained after wet spinning.

[0081] The added amount of the modified phase change material is 3.6wt% of the methyl cellulose content in the viscose spinning solution.

[0082] The viscose spinning solution has a methyl cellulose content of 6 wt %, an alkali content of 4.7 wt %, a viscosity of 60 mPa.s at room temperature, and a maturity of 14 ml (10% ammonium chloride).

[0083] Example 2

[0084] S1. Preparation of nanoporous hydroxyapatite microspheres

[0085] Span-80 was added to cyclohexane and stirred for 10 minutes to obtain an oil phase. Ammonium dihydrogen phosphate solution with adjusted pH was added to the oil phase and quickly stirred for 20 minutes to obtain an emulsion. The emulsion was added to calcium nitrate tetrahydrate solution and stirred for 10 minutes, then heated to 38°C in a water bath and reacted while stirring. After the reaction was completed, a crude product was obtained by rotary evaporation and centrifugation. The crude product was washed with cyclohexane, acetone and anhydrous ethanol in turn, and vacuum dried to obtain nanoporous hydroxyapatite microspheres.

[0086] The volume ratio of span-80 to cyclohexane is 1:15.

[0087] The pH of the diammonium phosphate solution was adjusted using a 0.6 mol / L ammonia solution.

[0088] The concentration of the diammonium phosphate solution is 0.3 mol / L, and the pH is 10.

[0089] The mass ratio of the diammonium phosphate solution to the oil phase is 1:1.7.

[0090] The concentration of the calcium nitrate tetrahydrate solution is 0.4 mol / L, and the mass ratio of the calcium nitrate tetrahydrate solution to the emulsion is 1.8:1.

[0091] The reaction time is 20 h.

[0092] The stirring rate is 400 r / min, and the rapid stirring rate is 1100 r / min.

[0093] The nanoporous hydroxyapatite microspheres have an average particle size of 230 nm and a porosity of 75%.

[0094] S2. Preparation of core materials

[0095] The phase change material is dissolved in chloroform, and then nanoporous hydroxyapatite microspheres are added and stirred for 20 minutes. After standing for 1 hour, the phase change material is adsorbed in the porous structure of the nanoporous hydroxyapatite microspheres. The core material is obtained by reduced pressure evaporation, filtration and drying.

[0096] The phase change material is stearic acid.

[0097] The volume ratio of the phase change material to chloroform is 1:7.

[0098] The added amount of the nanoporous hydroxyapatite microspheres is 24% of the mass of the phase change material.

[0099] The temperature of the reduced pressure evaporation is 50° C. and the time is 30 min.

[0100] The drying temperature is 70° C. and the drying time is 8 hours.

[0101] S3. Preparation of shell materials

[0102] Add polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene and perform azeotropic distillation to remove water, then evaporate the toluene, cool to room temperature, add dichloromethane under nitrogen protection until the system is clarified, and then drop acid-binding agent triethylamine and acryloyl chloride to the system in sequence under ice bath conditions. After the dropwise addition is completed, react at room temperature for 24 hours to modify unsaturated double bonds in the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer. After the reaction is completed, pour into ether for precipitation, filter, redissolve the precipitated product in dichloromethane, and then precipitate with ether, filter and dry to obtain the shell material.

[0103] The volume ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene is 1:3; the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer was purchased from Guangzhou Carbon Water Technology Co., Ltd.

[0104] The temperature of the ice bath was 4°C.

[0105] The molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, triethylamine and acryloyl chloride is 1:8:8.

[0106] The dropping rate is 2 ml / min.

[0107] The drying temperature is 60° C. and the drying time is 8 hours.

[0108] S4. Preparation of modified phase change materials

[0109] The core material and the shell material are added into distilled water and stirred, and ammonium cerium nitrate is added and ultrasonically reacted for 2 hours under nitrogen protection. After the reaction, the modified phase change material is obtained by centrifugation, filtration, water washing and drying.

[0110] The mass ratio of the core material to the shell material is 30:13; the added amount of the ammonium cerium nitrate is 1.6% of the shell material.

[0111] The drying temperature is 70° C. and the drying time is 8 hours.

[0112] The temperature of the ultrasonic reaction was 40°C and the frequency was 160 kHz

[0113] S5. Spinning

[0114] The modified phase change material was added into the viscose spinning solution and uniformly mixed for 20 minutes, and the phase change thermal insulation fiber was obtained after wet spinning.

[0115] The added amount of the modified phase change material is 2wt% of the acetone content in the viscose spinning solution.

[0116] The viscose spinning solution has a methyl cellulose content of 6 wt %, an alkali content of 4.7 wt %, a viscosity of 60 mPa.s at room temperature, and a maturity of 14 ml (10% ammonium chloride).

[0117] Example 3

[0118] S1. Preparation of nanoporous hydroxyapatite microspheres

[0119] Span-80 was added to cyclohexane and stirred for 20 minutes to obtain an oil phase. Ammonium dihydrogen phosphate solution with adjusted pH was added to the oil phase and quickly stirred for 30 minutes to obtain an emulsion. The emulsion was added to calcium nitrate tetrahydrate solution and stirred for 20 minutes, then heated to 45°C in a water bath and reacted while stirring. After the reaction was completed, a crude product was obtained by rotary evaporation and centrifugation. The crude product was washed with cyclohexane, acetone and anhydrous ethanol in turn, and vacuum dried to obtain nanoporous hydroxyapatite microspheres.

[0120] The volume ratio of span-80 to cyclohexane is 1:18.

[0121] The pH of the diammonium phosphate solution was adjusted using a 0.6 mol / L ammonia solution.

[0122] The concentration of the diammonium phosphate solution is 0.5 mol / L, and the pH is 11.

[0123] The mass ratio of the diammonium phosphate solution to the oil phase is 1:2.1.

[0124] The concentration of the calcium nitrate tetrahydrate solution is 0.6 mol / L, and the mass ratio of the calcium nitrate tetrahydrate solution to the emulsion is 2.2:1.

[0125] The reaction time is 28h.

[0126] The stirring rate is 600 r / min, and the rapid stirring rate is 1300 r / min.

[0127] The nanoporous hydroxyapatite microspheres have an average particle size of 160 nm and a porosity of 78%.

[0128] S2. Preparation of core materials

[0129] The phase change material is dissolved in chloroform, and then nanoporous hydroxyapatite microspheres are added and stirred for 30 minutes. After standing for 2 hours, the phase change material is adsorbed in the porous structure of the nanoporous hydroxyapatite microspheres. The core material is obtained by reduced pressure evaporation, filtration and drying.

[0130] The phase change material is stearic acid.

[0131] The volume ratio of the phase change material to chloroform is 1:9.

[0132] The added amount of the nanoporous hydroxyapatite microspheres is 32% of the mass of the phase change material.

[0133] The temperature of the reduced pressure evaporation is 60° C. and the time is 20 min.

[0134] The drying temperature is 80° C. and the drying time is 6 hours.

[0135] S3. Preparation of shell materials

[0136] Add polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene and perform azeotropic distillation to remove water, then evaporate the toluene, cool to room temperature, add dichloromethane under nitrogen protection until the system is clarified, and then drop acid-binding agent triethylamine and acryloyl chloride to the system in sequence under ice bath conditions. After the dropwise addition is completed, react at room temperature for 36 hours to modify unsaturated double bonds in the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer. After the reaction is completed, pour into ether for precipitation, filter, redissolve the precipitated product in dichloromethane, and then precipitate with ether, filter and dry to obtain the shell material.

[0137] The volume ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene is 1:5; the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer was purchased from Guangzhou Carbon Water Technology Co., Ltd.

[0138] The temperature of the ice bath was 8°C.

[0139] The molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, triethylamine and acryloyl chloride is 1:10:10.

[0140] The dropping rate is 5 ml / min.

[0141] The drying temperature is 70° C. and the drying time is 6 hours.

[0142] S4. Preparation of modified phase change materials

[0143] The core material and the shell material are added into distilled water and stirred, and ammonium cerium nitrate is added and ultrasonically reacted for 3 hours under nitrogen protection. After the reaction, the modified phase change material is obtained by centrifugation, filtration, water washing and drying.

[0144] The mass ratio of the core material to the shell material is 40:17; the added amount of the ammonium cerium nitrate is 2.4% of the shell material.

[0145] The drying temperature is 80° C. and the drying time is 6 hours.

[0146] The temperature of the ultrasonic reaction is 45° C. and the frequency is 120 kHz.

[0147] S5. Spinning

[0148] The modified phase change material was added into the viscose spinning solution and uniformly mixed for 20 minutes, and the phase change thermal insulation fiber was obtained after wet spinning.

[0149] The added amount of the modified phase change material is 5wt% of the acetone content in the viscose spinning solution.

[0150] The viscose spinning solution has a methyl cellulose content of 6 wt %, an alkali content of 4.7 wt %, a viscosity of 60 mPa.s at room temperature, and a maturity of 14 ml (10% ammonium chloride).

[0151] Comparative Example 1

[0152] Representative Example 1 was selected, S3 was removed, and an equal amount of core material was directly added to the viscose spinning solution. The rest was consistent with Example 1, as Comparative Example 1.

[0153] Comparative Example 2

[0154] Representative Example 1 was selected, S1, S2, and S3 were removed, and an equal amount of phase change material was directly added to the viscose spinning solution. The rest was consistent with Example 1, as Comparative Example 2.

[0155] The performance of the phase change thermal insulation fibers prepared in the examples and comparative examples was tested, as shown in Table 1.

[0156] Table 1

[0157]

[0158] In Comparative Example 1, an equal amount of core material is directly added to the viscose spinning solution, and various properties are reduced, but the performance is better than that of Comparative Example 2, indicating that the core material has a certain adsorption effect on the phase change material, and the heat transfer loss rate after 50 washings is lower than that of Comparative Example 2; while the dispersion and compatibility of the phase change material and the core material in the fiber are poor, the modified phase change material has better dispersion and compatibility with the fiber, so the mechanical properties of the fiber of Example 1 are also better, and the heat transfer loss rate of Example 1 after 50 washings is lower, indicating that the shell-core structure of the modified phase change material plays a certain protective role on the phase change material, so the washing loss rate is lower, and the thermal insulation function is more durable.

[0159] Note:

[0160] Heat transfer coefficient test standard: GB / T 35762-2017;

[0161] Thermal insulation rate test standard: GB / T 35762-2017;

[0162] Heat transfer loss rate after 50 water washings = (heat transfer coefficient after 50 water washings - heat transfer coefficient) / heat transfer coefficient × 100%.

[0163] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.

[0164] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a phase-change thermal insulation fiber based on a porous structure, characterized in that: The preparation method comprises the preparation of nano porous hydroxyapatite microspheres, the preparation of core materials, the preparation of shell materials, the preparation of modified phase change materials and spinning.

2. The method for preparing a phase change thermal insulation fiber based on a porous structure according to claim 1, characterized in that: The preparation method of the nanoporous hydroxyapatite microspheres comprises the following steps: adding span-80 to cyclohexane and stirring for 10 to 20 minutes to obtain an oil phase; adding a diammonium phosphate solution with a pH adjusted to the oil phase and rapidly stirring for 20 to 30 minutes to obtain an emulsion; adding the emulsion to a calcium nitrate tetrahydrate solution and stirring for 10 to 20 minutes; then heating the solution in a water bath to 38 to 45° C. and reacting while stirring; after the reaction is completed, rotary evaporation and centrifugation are performed to obtain a crude product; the crude product is washed with cyclohexane, acetone and anhydrous ethanol in sequence; and vacuum drying is performed to obtain the nanoporous hydroxyapatite microspheres.

3. The method for preparing a phase change thermal insulation fiber based on a porous structure according to claim 2, characterized in that: The volume ratio of span-80 to cyclohexane is 1:15-18; The concentration of the diammonium phosphate solution is 0.3-0.5 mol / L, and the pH is 10-11; The mass ratio of the diammonium phosphate solution to the oil phase is 1:1.7-2.1; The concentration of the calcium nitrate tetrahydrate solution is 0.4-0.6 mol / L, and the mass ratio of the calcium nitrate tetrahydrate solution to the emulsion is 1.8-2.2:1; The reaction time is 20 to 28 hours; The stirring rate is 400-600 r / min, and the rapid stirring rate is 1100-1300 r / min; The nano porous hydroxyapatite microspheres have an average particle size of 160-230 nm and a porosity of 75-82%.

4. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 1, characterized in that: The core material is prepared by dissolving the phase change material in chloroform, adding nanoporous hydroxyapatite microspheres, stirring for 20 to 30 minutes, standing for 1 to 2 hours, evaporating under reduced pressure, filtering, and drying to obtain the core material; The phase change material is one or more of stearic acid, hexadecane and octadecane; The volume ratio of the phase change material to chloroform is 1:7-9; The added amount of the nanoporous hydroxyapatite microspheres is 24-32% of the mass of the phase change material.

5. The method for preparing a phase change thermal insulation fiber based on a porous structure according to claim 1, characterized in that: The shell material is prepared by adding a polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene, performing azeotropic distillation to remove water, then distilling off toluene, cooling to room temperature, adding dichloromethane under nitrogen protection until the system is clarified, and then dripping acid-binding agents triethylamine and acryloyl chloride into the system in sequence under ice bath conditions, reacting at room temperature for 24 to 36 hours after the dripping is completed, modifying unsaturated double bonds in the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, pouring into ether for precipitation after the reaction is completed, filtering, re-dissolving the precipitated product in dichloromethane, and then precipitating with ether, filtering, and drying to obtain the shell material.

6. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 5, characterized in that: The volume ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to toluene is 1:3-5; The temperature of the ice bath is 4-8°C; The molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, triethylamine and acryloyl chloride is 1:8-10:8-10; The drop acceleration rate is 2 to 5 ml / min; The drying temperature is 60-70° C. and the drying time is 6-8 hours.

7. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 1, characterized in that: The modified phase change material is prepared by adding the core material and the shell material into distilled water and stirring, adding ammonium cerium nitrate and reacting under nitrogen protection for 2 to 3 hours by ultrasonication, and after the reaction, centrifuging, filtering, washing with water, and drying to obtain the modified phase change material.

8. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 7, characterized in that: The mass ratio of the core material to the shell material is 30-40:13-17; the amount of the ammonium cerium nitrate added is 1.6-2.4% of the shell material; The temperature of the ultrasonic reaction is 40-45° C., and the frequency is 120-160 kHz.

9. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 1, characterized in that: The spinning is to add the modified phase change material into the spinning solution or the polymer slices and mix them evenly, and then obtain the phase change thermal insulation fiber through wet spinning or melt spinning.

10. The method for preparing a phase-change thermal insulation fiber based on a porous structure according to claim 9, characterized in that: The spinning solution is one of a viscose spinning solution and a polyacrylonitrile spinning solution; The polymer slice is one of PP slice, PET slice and PA6 slice; The added amount of the modified phase change material is 2-5 wt % of the effective ingredients or polymer chips in the spinning solution.